Optimization of Enzymatic Hydrolysis of Viscera Proteins of Rainbow Trout (Oncorhynchus mykiss) (2018)
ABSTRACT: This study aimed to optimize the enzymatic hydrolysis of rainbow trout (Oncorhynchus mykiss) viscera with the enzyme alcalase® 2.4 L to found the highest the Degree of Hydrolysis (DH). In vitro evaluation of the optimum conditions (pH and temperature) was performed to maximize the Proteolytic Activity (PA) of alcalase® 2.4 L with the rainbow trout viscera. The optimal conditions for maximum enzymatic activity were a pH of 8.5 and a temperature of 60°C. Response Surface Methodology (RSM) was used to evaluate the effect of the enzyme/substrate ratio (10-30%), substrate concentration (2.0-6.0%) and temperature (45-65°C) on DH. A substrate concentration of 5.53% and an enzyme/substrate level of 30% were found to be the optimum conditions to obtain the highest DH (27.6%). The Michaelis-Menten plot indicated that these conditions were not in the saturation area.